Hypothalamic Vasopressinergic Projections Innervate Central Amygdala GABAergic Neurons: Implications for Anxiety and Stress Coping - Hernández, Vito S.; Hernández, Oscar R.; Perez de la Mora, Miguel; Gómora, María J.; Fuxe, Kjell; Eiden, Lee E.; Zhang, Limei (Frontiers in Neural Circuits, 2016)
The arginine-vasopressin (AVP)-containing hypothalamic magnocellular neurosecretory neurons (VPMNNs) are known for their role in hydro-electrolytic balance control via their projections to neurohypophysis. Recently, projections from these same neurons to hippocampus, habenula, and other brain regions, in which vasopressin infusion modulates contingent social and emotionally-affected behaviors, have been reported. Here, we present evidence that VPMNN collaterals also project to the amygdaloid complex, and establish synaptic connections with neurons in central amygdala (CeA). The density of AVP innervation in amygdala was substantially increased in adult rats that had experienced neonatal maternal separation (MS), consistent with our previous observations that MS enhances VPMNN number in the paraventricular (PVN) and supraoptic (SON) nuclei of the hypothalamus. In the CeA, V1a AVP receptor mRNA was only observed in GABAergic neurons, demonstrated by complete co-localization of V1a transcripts in neurons expressing Gad1 and Gad2 transcripts in CeA using the RNAscope method. V1b and V2 receptors mRNA were not detected, using the same method. Water-deprivation for 24 hrs, which increased the metabolic activity of VPMNNs, also increased anxiety-like behavior measured using the elevated plus maze test, and this effect was mimicked by bilateral microinfusion of VP into the CeA. Anxious behavior induced by either water deprivation or VP infusion was reversed by CeA infusion of V1a antagonist. VPMNNs are thus a newly discovered source of central amygdala inhibitory circuit modulation, through which both early-life and adult stress coping signals are conveyed from the hypothalamus to the amygdala.